Three new isoflavones from the Pueraria montana var. lobata (Willd.) and their bioactivities. Issue 23 (2nd December 2018) - Cui, Tinghui; Tang, Shiyun; Liu, Chunbo; Li, Zhenjie; Zhu, Qin; You, Junheng; Si, Xiaoxi; Zhang, Fengmei; He, Pei; Liu, Zhihua; Miao, Mingming; Yang, Guangyu; et al.
Abstract: Three new isoflavones, 7-acetyl-4′, 6-dimethoxy-isoflavone (1 ), 7-acetyl-4′-hydroxy-6-methoxy-isoflavone (2 ) and 7-acetyl-6, 8-dimethoxy-4′-hydroxy-isoflavone (3 ), together with five known flavones (4 –8 ), were isolated from the Pueraria montana var. lobata (Willd.). Their structures were elucidated by spectroscopic methods, including extensive 1D- and 2D NMR techniques. Compounds1 –8 were evaluated for their anti-tobacco mosaic virus (anti-TMV) activities. The results showed that compounds1 and2 exhibited high anti-TMV activities with inhibition rates of 36.8 and 33.6%, respectively. The inhibition rates are higher than that of positive control. The other compounds also showed potential anti-TMV activities with inhibition rates in the range of 21.8~28.4%, respectively. The cytotoxicities of compounds1 –3 against five human tumour cell lines (NB4, A549, SHSY5Y, PC3 and MCF7) were also tested. The results revealed that compounds1 –3 showed weak inhibitory activities against some tested human tumour cell lines with IC50 values in the range of 1.2–3.6 μM. Abstract :